The paediatric training required by the general practitioner: A report by a Joint Working Party of The British Paediatric Association and The Royal College of General Practitioners (1976)
This report has been written because special programmes of training for general practice are being developed in many parts of the country and there are questions about the paediatric component of training which need to be discussed nationally. An important part of this report is devoted to listing educational objectives which should be attained in paediatrics by the general practitioner at the end of his training.